Structural changes in S. epidermidis biofilms after transmission between stainless steel surfaces. Issue 9 (21st October 2017) - Gusnaniar, Niar; Sjollema, Jelmer; Nuryastuti, Titik; Peterson, Brandon W.; van de Belt-Gritter, Betsy; de Jong, Ed D.; van der Mei, Henny C.; Busscher, Henk J.
Abstract: Transmission is a main route for bacterial contamination, involving bacterial detachment from a donor and adhesion to receiver surfaces. This work aimed to compare transmission of an extracellular polymeric substance (EPS) producing and a non-EPS producing Staphylococcus epidermidis strain from biofilms on stainless steel. After transmission, donor surfaces remained fully covered with biofilm, indicating transmission through cohesive failure in the biofilm. Counter to the numbers of biofilm bacteria, the donor and receiver biofilm thicknesses did not add up to the pre-transmission donor biofilm thickness, suggesting more compact biofilms after transmission, especially for non-EPS producing staphylococci. Accordingly, staphylococcal density per unit biofilm volume had increased from 0.20 to 0.52 μm –3 for transmission of the non-EPS producing strain under high contact pressure. The EPS producing strain had similar densities before and after transmission (0.17 μm –3 ). This suggests three phases in biofilm transmission: (1) compression, (2) separation and (3) relaxation of biofilm structure to its pre-transmission density in EPS-rich biofilms.